Advanced predictive models for thyroid disease comorbidities using machine learning and deep learning: a comprehensive review - Yacoob B. A., Mohammed; J., Jayashree (Institute of Advanced Engineering and Science, 2025)
With advances in machine learning (ML) and deep learning (DL), the future of thyroid disease diagnosis and prognosis looks very bright. The integration of various data such as imaging and medical record data has increased the accuracy of the model. Advanced DL models such as convolutional neural network (CNN) and recurrent neural network (RNN) further improved disease detection in precision medicine. However, some of the major disadvantages of effective clinical integration include unbalanced samples, unclear sampling, having to communicate in different populations, decreased physician confidence due to the vagueness of current models therefore, and few studies available to identify thyroid comorbidities such as polycystic ovary syndrome (PCOS) and thyroid eye disease (TED) in a variety of different populations to develop the line. It is important to focus future research activities on model definition and validation an improving and thus the diagnosis and prognosis of thyroid comorbidities is of utmost importance. What this will bring is ML and DL, an opportunity to make very significant improvements in the diagnosis, treatment, and management of thyroid diseases, thereby improving patient outcomes and health care by seeking crystals as a group they work interdisciplinary to collaborate in developing flexible solutions, sharing knowledge, and responding to these stated deficiencies.